Plagiarism in higher education : tackling tough topics in academic integrity - Eaton, Sarah Elaine (Libraries Unlimited, 2021)
"This candid treatment of plagiarism in higher education identifies causes of academic dishonesty and offers practical solutions"- Resumé vydavatel
Keywords: plagiátorství; vysokoškolské studium -- etické a morální aspekty; vysokoškolští učitelé; etika povolání; plagiarism; college study -- ethical and moral aspects; college teachers; professional ethics; elektronické knihy; monografie; electronic books; monographs